2023
DOI: 10.1039/d2fo01096h
|View full text |Cite
|
Sign up to set email alerts
|

Inulin: properties and health benefits

Abstract: Inulin, as a soluble dietary fiber, is widely found in beyond 36,000 plant species as reserve polysaccharides. The primary sources of inulin include Jerusalem artichoke, chicory, onion, garlic, barley, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 136 publications
0
15
0
Order By: Relevance
“…These 2 polysaccharides are widely known for their antiinflammatory properties. 16,43 We found that both could reverse the increases in ALT, TNFα, and TGFβ1, but only oat βglucan could lower the liver index, AST, and insulin. The improvement in liver injury and hepatic inflammation resulting from oat β-glucan and inulin supplementation was consistent with previous studies that investigated their capability to prevent NAFLD, 24,26,44 implying that these 2 polysaccharides can be utilized in NAFLD prevention and treatment.…”
Section: Discussionmentioning
confidence: 72%
“…These 2 polysaccharides are widely known for their antiinflammatory properties. 16,43 We found that both could reverse the increases in ALT, TNFα, and TGFβ1, but only oat βglucan could lower the liver index, AST, and insulin. The improvement in liver injury and hepatic inflammation resulting from oat β-glucan and inulin supplementation was consistent with previous studies that investigated their capability to prevent NAFLD, 24,26,44 implying that these 2 polysaccharides can be utilized in NAFLD prevention and treatment.…”
Section: Discussionmentioning
confidence: 72%
“…Fermentation of dietary components and their gut microbiome and metabolome effects are often investigated in isolation, whereas product formulations often contain blends of several functional ingredients. For example, research has been separately conducted on the beneficial effects of prebiotic fibers (Makki et al ., 2018; Qin et al ., 2023) and to a lesser extent for botanicals (Cefalu, Ye and Wang, 2008; Choi et al ., 2020; Xu et al ., 2022) but, to our knowledge, no research is published on the synergistic effects of both functional ingredient categories. To this end, we investigated this concept by employing OLIPOP, a widely consumed functional soda containing a mixture of 3 fibers and 4 botanicals, in in vitro fermentations of the prebiotic fibers in OLIPOP with and without the paired botanicals.…”
Section: Discussionmentioning
confidence: 99%
“…73 In addition, inulin also exhibits excellent health benefits in glycolipid metabolism, inhibiting the expression of inflammatory factors, enhancing mineral absorption, and improving constipation. 74 The structure of related polysaccharide compounds is shown in Figure 4.…”
Section: Saccharidesmentioning
confidence: 99%